ZC3H12A (MCPIP1): Molecular characteristics and clinical implications (2010)
Background: ZC3H12A is a gene whose absence is related to autoimmune disorders and to other phenotypical alterations. Methods: A comprehensive review of the structure, molecular functions and regulation of ZC3H12A gene and its protein MCPIP1 is done in order to understand their clinical implications. Results: ZC3H12A, at 1p34.3, has 9860 bp, six exons and 61 described SNPs. Eleven are non-synonymous thus leading to changes in MCPIP1, the protein encoded by ZC3H12A. MCPIP1 is induced by MCP-1 and IL-1 whose signals are transduced through the NF-k? and MAPkinase pathways. This protein acts as an RNAse by degrading chemokine transcripts such as IL-1 as well as its own mRNA and as a transcription factor by reducing the expression of other chemokines induced by NF-k? such as MCP-1. It also up-regulates genes involved in several differentiation processes and apoptosis. Therefore, ZC3H12A is an equilibrium gatekeeper that not only regulates its own inducers but also controls the regulation by degrading its own mRNA. Conclusion: Understanding ZC3H12A gives a comprehensive panorama that promises to improve our understanding of processes in which this gene is involved including autoimmune, infectious and cardiovascular diseases. © 2010 Elsevier B.V.